2015
DOI: 10.1016/j.molcata.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

A fluorine free method to synthesize nitrogen and lanthanum co-doped TiO2 nanocrystals with exposed {001} facets for enhancing visible-light photocatalytic activity

Abstract: a b s t r a c tThis study introduces a simple and fluorine free route to synthesize nitrogen and lanthanum co-doped TiO 2 nanocrystals with exposed {0 0 1} facets through one-step hydrothermal method. The microstructure, chemical composition, and photocatalytic property of the co-doped TiO 2 nanosheets were analyzed using XRD, FESEM, TEM, XPS and UV-vis. The experimental results indicated that N had been successfully doped into TiO 2 lattice, while La was likely to form a binary nanocomposite with TiO 2 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In addition, it has been widely reported that surface O molecules on the {001} facets are unstable and very reactive, which leads to more oxygen vacancies on the exposed {001} facets . The defects caused by these oxygen vacancies can provide sites for the photogenerated holes to react with dissociated water molecules and hydroxyl groups, thus forming ·OH radicals (eqs and ): …”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been widely reported that surface O molecules on the {001} facets are unstable and very reactive, which leads to more oxygen vacancies on the exposed {001} facets . The defects caused by these oxygen vacancies can provide sites for the photogenerated holes to react with dissociated water molecules and hydroxyl groups, thus forming ·OH radicals (eqs and ): …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the photocatalytic activities of all of the La-doped TiO 2 nanosheet films were considerably higher than that of the pure TiO 2 nanosheet film. It is important to note that the 1.0 mol-% La-doped TiO 2 nanosheets films with 87 % of the {001} facets exhibit much higher photocatalytic activities than those of the pure TiO 2 nanosheet films for both MB and MO To compare the photocatalytic activities quantitatively, the apparent rate constants (k app ) for the photocatalytic oxidation of MB and MO over the samples were evaluated for a pseudofirst-order model, [30] as shown in Figure 5 (b and d). The apparent rate constant is given by ln(C 0 /C t ) = k app t; C t is the solutionphase concentration of the dye, and C 0 is the initial concentration at t = 0.…”
Section: Resultsmentioning
confidence: 99%
“…First, the unique mesoporous structure and higher surface area of DE would significantly improve the adsorption capacity of the material, providing a more active adsorption site towards the target molecules. Second, the incorporation of ZnTiO 3 /TiO 2 and ZnTiO 3 /TiO 2 /La photocatalysts could facilitate transfer of photogenerated electrons from the bulk to the surface and thus inhibit the recombination of electron pairs and holes under solar irradiation [ 38 ]. As is known, under illumination, the electrons of a photocatalyst can be excited and then immediately transferred from the valence band (VB) to the conduction band (CB), generating an electron-hole pair (e − /h + ) and leaving a hole (h + ) in the VB (reaction R1).…”
Section: Discussionmentioning
confidence: 99%
“…The photocatalytic activity of semiconductors is influenced by a wide variety of factors such as morphology, specific surface area, affinity and adsorption capacity of organic pollutants, intensity and spectral distribution of the illuminating light, and pH of the solutions, among others [ 35 ]. Among the many semiconductors, TiO 2 nanostructures have drawn increasing interest in wastewater treatment [ 36 , 37 ] due to several attractive properties including high reactivity, chemical stability, high oxidative capacity, non-toxicity, and low cost [ 38 , 39 , 40 , 41 ]. However, TiO 2 has some disadvantages that hinder its cost-effectiveness and applicability, such as a wide bandgap (~3.2 eV), which limits its activity to a small proportion of the solar spectrum in the ultraviolet region.…”
Section: Introductionmentioning
confidence: 99%